Identifikasi Senyawa Bioaktif Ekstrak Alga Coklat (Hormophysa triquetra) - Sriyati Sampulawa; Farida Bahalwan (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Hormophysa triquetra is a type of brown algae that is easily found along the coast with sandy and rocky sediments. Based on the results of research, some brown algae are known to be often used because they are a rich source of various secondary metabolites. Hormophysa triquetra is a type of brown algae that needs to be investigated for the content of secondary metabolites so that it can be used widely. The research method used is an experimental method with sampling techniques carried out using free samples, which were carried out in the waters of Hutumuri Village, Ambon City, the samples obtained were then dried by aerating, then the algae samples were extracted by the maceration method, then the results of the Hormophysa extract triquetra carried out phytochemical tests. Phytochemical test of Hormophysa triquetra extract included examination of the content of alkaloids, flavonoids, tannins, terpenoids/steroids and saponins. The test results showed that the Hormophysa triquetra algae extract contained flavonoid, terpenoid, phenolic, saponin and alkaloid compounds.